Potencial da extração de óleo de peixe para produção de biodiesel - Martins, Gislaine Iastiaque (2012)
Energy issues have been discussed intensively in the search for alternative energy sources, environmentally friendly and sustainable, since the prospect of depletion of fossil fuel reserves are eminent, thus reviving attention to alternative energy sources, among them, biofuels. Fish oil shows up as an alternative technology for the recovery of waste from processing of tilapia, as a way to add value to this material, with a focus on cleantech. Thus, the present study aimed to evaluate the performance and acidity of the oil tilapia depending on the type of fish waste, indicate a methodology that promotes neutralizing the acidity of the oil, produce and characterize physicochemically biodiesel fish through the process transesterification via base catalysis, methylic route and compare the results with the parameters set as mandatory for the commercialization of biodiesel used in the national territory, by Resolution No. 07, 19.3.2008 - 20.3.2008 DOU National Agency of Petroleum, Natural Gas and (ANP). By the method used was not possible to obtain oil from the scales and skin of Tilapia. The viscera had oil content of 22% and the mixture of waste presented oil content of 6.12%. The oil obtained showed the viscera acid number unsuitable for the production of biodiesel transesterification process, thus necessitating undergo a neutralization process for its transformation into biodiesel. The other had acid value waste suitable for transesterification and biodiesel production. The neutralization process with continuous separation of oil-sludge system with filtering paper filter was effective in neutralizing the acidity of the fish oil, favoring the use of raw materials and high acidity oils, neutralized oil in a yield of about 80% and providing the fish oil, after the neutralization process can be transesterified via base catalysis for biodiesel production. The analysis of the calorific value of biodiesel showed similar to petroleum diesel, biodiesel values that give the fish a good combustibility compared to diesel fuel, some parameters characterize physicochemically biodiesel fish according to the specifications laid down in Resolution No. 07/ANP, indicating that fish oil is promising for producing biodiesel via transesterification reaction process